GGC Repeat Expansion of RILPL1 is Associated with Oculopharyngodistal Myopathy - Zeng, Yi‐Heng; Yang, Kang; Du, Gan‐Qin; Chen, Yi‐Kun; Cao, Chun‐Yan; Qiu, Yu‐Sen; He, Jin; Lv, Hai‐Dong; Qu, Qian‐Qian; Chen, Jian‐Nan; Xu, Guo‐Rong; Chen, Long; et al. (Annals of neurology, 2022)
Objective Oculopharyngodistal myopathy (OPDM) is an adult‐onset neuromuscular disease characterized by progressive ptosis, dysarthria, ophthalmoplegia, and distal muscle weakness. Recent studies revealed that GGC repeat expansions in 5′‐UTR of LRP12, GIPC1, and NOTCH2NLC are associated with OPDM. Despite these advances, approximately 30% of OPDM patients remain genetically undiagnosed. Herein, we aim to investigate the genetic basis for undiagnosed OPDM patients in two unrelated Chinese Han families. Methods Parametric linkage analysis was performed. Long‐read sequencing followed by repeat‐primed polymerase chain reaction and amplicon length polymerase chain reaction were used to determine the genetic cause. Targeted methylation sequencing was implemented to detect epigenetic changes. The possible pathogenesis mechanism was investigated by quantitative polymerase chain reaction, immunoblotting, RNA fluorescence in situ hybridization, and immunofluorescence staining of muscle biopsy samples. Results The disease locus was mapped to 12q24.3. Subsequently, GGC repeat expansion in the promoter region of RILPL1 was identified in six OPDM patients from two families, findings consistent with a founder effect, designated as OPDM type 4. Targeted methylation sequencing revealed hypermethylation at the RILPL1 locus in unaffected individuals with ultralong expansion. Analysis of muscle samples showed no significant differences in RILPL1 mRNA or RILPL1 protein levels between patients and controls. Public CAGE‐seq data indicated that alternative transcription start sites exist upstream of the RefSeq‐annotated RILPL1 transcription start site. Strand‐specific RNA‐seq data revealed bidirectional transcription from the RILPL1 locus. Finally, fluorescence in situ hybridization/immunofluorescence staining showed that both sense and antisense transcripts formed RNA foci, and were co‐localized with hnRNPA2B1 and p62 in the intranuclear inclusions of OPDM type 4 patients. Interpretation Our findings implicate abnormal GGC repeat expansions in the promoter region of RILPL1 as a novel genetic cause for OPDM, and suggest a methylation mechanism and a potential RNA toxicity mechanism are involved in OPDM type 4 pathogenesis. ANN NEUROL 2022;92:512–526